Honor Among Thieves: Open Internal Reporting and Managerial Collusion - Evans, John H.; Moser, Donald V.; Newman, Andrew H.; Stikeleather, Bryan R. (Contemporary Accounting Research, 2016)
Firms have increasingly adopted open work environments. Although openness is thought to have benefits, it could also expose firms to an unanticipated cost. An open (closed) internal reporting environment makes it more (less) likely that managers will observe a colleague's communications with senior executives. This increase in what one manager knows about another manager's communication to senior executives could facilitate employee collusion to extract resources from the firm. To test whether internal reporting openness results in more collusion, we conduct an experiment in which two managers each make separate reports to the firm about cost information they know in common but that remains unknown by the firm. Because both managers face the same truth‐inducing contract, conventional economic theory predicts that they will not collude to misreport costs regardless of reporting openness. However, using behavioral theory involving trust and reciprocity, we predict and find that managers honor their nonbinding collusive agreements and successfully collude more often in an open versus closed internal reporting environment, leading to lower firm welfare in the open environment. These results suggest that firms should consider how the cost of collusion compares to the benefits of openness.